Clinical and laboratory profiles of pediatric asthma patients with house dust mite (HDM)–specific subcutaneous immunotherapy: A single center, cross sectional study - Desy Wulandari; Wisnu Barlianto (Medical Faculty of Brawijaya University, Indonesia, 2022)
Introduction: House dust mite (HDM) allergy has been reported as an actual cause of asthma in children. Subcutaneous immunotherapy (SCIT) is a recommended treatment for HDM allergy patients. However, there were limited data about the characteristic of pediatric patients with HDM-SCIT, particularly in Indonesia. This study was aimed to evaluate the characteristic of pediatric patients with allergic asthma. Methods: Study participants were pediatric patients confirmed with HDM allergy from Skin Prick Test (SPT) in the pediatric allergy-immunology outpatient clinic in Saiful Anwar Hospital Malang, Indonesia. Patients who were treated with HDM-SCIT in the early build-up phase of treatment were included in this study. Demographic and clinical characteristics of the patients were recorded. Peripheral blood samples were drawn to evaluate the total eosinophil count (TEC), total basophil count (TBC), neutrophil-lymphocyte ratio (NLR), specific IgE (sIgE) and total IgE (t-IgE) level. Clinical diagnosis of asthma was classified according to the Global Initiative for Asthma (GINA) criteria. The evaluation of asthma control was assessed by the Asthma Control Test (ACT) score. Results: Thirty-two patients were enrolled in this study, including 14 male and 18 female. The mean age of children was 6.92 ± 2.60 years old. There were 21 subjects with uncontrolled asthma and 11 subjects with partially controlled asthma. Demographic characteristics including age, sex, nutritional status and family history were not significantly different between uncontrolled and partially controlled asthma groups (p> 0.05). TEC, TBC, NLR, and tIgE were not different significantly among groups (p> 0.05). This study showed that the mean of sIgE serum level was higher in uncontrolled asthma compared to partially controlled asthma group (p= 0.022). Moreover, it was a negative significant correlation between sIgE serum level and ACT score (p= 0.002, r= -0.532). Conclusion: Higher sIgE levels were correlated with poor asthma control in HDM-SCIT patients.